Rhizomelic Chondrodysplasia Punctata (RCDP) in a Newborn - Raha, Biplob Kumar; Haque, ZSM; Jahan, N; Begum, M; Hasan, M; Rob, AWS; Farhana, T; Yasmin, S; Hasnat, SKA; Islam, Z (Journal of Bangladesh College of Physicians and Surgeons, 2015)
A female newborn baby presented with the features of Rhizomelic chondrodysplasia Punctata (RCDP) characterized by rhizomalic shortening with contracture of lower extremities, ichthyosis, microcephaly, dysmorphic facial features including a depressed nasal bridge, hypoplastic midface, full cheeks & low set ear, breathing difficulties and anthropometric measures below the expected indexes for her age. The patient also presented congenital heart disease, a less common manifestation of the syndrome. Radiological features include epiphyseal stippling & Journal of Bangladesh College of Physicians and Surgeons Vol. 32, No. 3, July 2014 multiple calcification in the epiphyseal cartilage, metaphyseal flaring and clefts in vertebral bodies. It is a rare autosomal recessively inherited skeletal dysplasia. The prognosis is bad and death usually occurs within the first year of age. We report a case of neonatal RCDP which was diagnosed based on the typical clinical and radiological features. J Bangladesh Coll Phys Surg 2014; 32: 174-177